The Technology of Binaural Understanding - Blauert, Jens.; Braasch, Jonas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book offers a computational framework for modeling active exploratory listening that assigns meaning to auditory scenes. Understanding auditory perception and cognitive processes involved with our interaction with the world are of high relevance for a vast variety of ICT systems and applications. Human beings do not react according to what they perceive, but rather, they react on the grounds of what the percepts mean to them in their current action-specific, emotional and cognitive situation. Thus, while many models that mimic the signal processing involved in human visual and auditory processing have been proposed, these models cannot predict the experience and reactions of human users. This book presents a model that incorporates both signal-driven (bottom-up), and hypothesis-driven (top-down) processing.
Part 1: Forming and Interpreting Aural Objects: Effects and Models -- Part 2: Configuring and Understanding Aural-Space -- Part 3: Processing Cross-modal Inference -- Part 4: Evaluating Aural-scene Quality and Speech Understanding -- Part 5: Applying Cognitive Mechanisms in Audio Technology. .
Keywords: Acoustics; Acoustical engineering; Signal processing; Image processing; Speech processing systems; Acoustics; Engineering Acoustics; Signal, Image and Speech Processing